2006
DOI: 10.1152/jn.00563.2006
|View full text |Cite
|
Sign up to set email alerts
|

Predicting 2D Target Velocity Cannot Help 2D Motion Integration for Smooth Pursuit Initiation

Abstract: Montagnini, Anna, Miriam Spering, and Guillaume S. Masson. Predicting 2D target velocity cannot help 2D motion integration for smooth pursuit initiation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 21 publications
0
25
0
Order By: Relevance
“…On the face of it, this conclusion might appear to be different from that drawn by Montagnini et al (2006), who held that object motion was needed for anticipatory smooth eye movements to occur. However, object motion referred to different characteristics of motion in the two studies.…”
Section: Discussionmentioning
confidence: 61%
See 3 more Smart Citations
“…On the face of it, this conclusion might appear to be different from that drawn by Montagnini et al (2006), who held that object motion was needed for anticipatory smooth eye movements to occur. However, object motion referred to different characteristics of motion in the two studies.…”
Section: Discussionmentioning
confidence: 61%
“…One holds that anticipatory smooth eye movements in response to cues occur only under conditions where the expectations are able to generate salient representations of the expected motion (see Krauzlis, 2004 for a similar proposal with respect to the difficulty of generating imagined motion signals). On the basis of our results, we suggest that salient representations of the expected direction of motion, sufficient to drive anticipatory smooth eye movements, may be generated either from expectations of the sustained motion of objects, or expectations of the global motion of limited-lifetime RDKs (but perhaps not for the direction of the primitive and transient 1D motions studied by Montagnini et al, 2006). Cues about the lifetime of the elements (lifetime controls the signal/noise properties of the stimulus; Appendix A), on the other hand, may be ineffective because expectations about dot lifetime might not be helpful in constructing a perceptually salient representation of the expected motion.…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…The brain has to resolve this conflict and select one of the two birds for pursuit. A previous study showed that top-down knowledge about the two-dimensional motion direction of a tilted bar does not allow to compensate for the biased one-dimensional edge motion (Montagnini, Spering, & Masson, 2006). This finding suggests that bottom-up stimulus information can even override top-down expectations.…”
Section: Introductionmentioning
confidence: 90%